2005
DOI: 10.1016/j.ejcts.2005.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Complex pulmonary aspergilloma treated with single stage cavernostomy and myoplasty

Abstract: Objective: Complex pulmonary aspergilloma (CPA) following pulmonary tuberculosis may lead to massive and fatal hemoptysis. Pulmonary resection, as initial therapy, carries high morbidity and mortality. Resection is contraindicated in patients with compromised lung function (FEV1!40%) and in those with bilateral disease. We reviewed the results of patients undergoing single stage cavernostomy and myoplasty as an alternative therapy in patients with normal and compromised lung function. Methods: Patients sufferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
15
0
6
Order By: Relevance
“…Although lung resection is the optimal curative treatment for pulmonary aspergilloma, several authors have reported that single-stage cavernostomy and myoplasty is an effective alternative therapy for this condition, since Daly et al reported its use for the first time. [2][3][4] One reported cause of failure in this treatment is muscle flap disuse atrophy. 3) In our patient, the following were considered important for obtaining a successful result: 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lung resection is the optimal curative treatment for pulmonary aspergilloma, several authors have reported that single-stage cavernostomy and myoplasty is an effective alternative therapy for this condition, since Daly et al reported its use for the first time. [2][3][4] One reported cause of failure in this treatment is muscle flap disuse atrophy. 3) In our patient, the following were considered important for obtaining a successful result: 1.…”
Section: Discussionmentioning
confidence: 99%
“…1) Therefore, successful results of single-stage cavernostomy and myoplasty as palliative therapy for these high-risk patients have been reported by several authors. [2][3][4] In this form of treatment, muscle flap disuse atrophy is sometimes a cause of failure. Here, we report a case of pulmonary aspergilloma that was treated successfully by limited thoracoplasty with simultaneous single-stage cavernostomy and a muscle transposition flap, and review the relevant literature.…”
Section: Introductionmentioning
confidence: 99%
“…(3,5,9,(10)(11)(12) Surgical mortality and morbidity are related to the type of pulmonary aspergilloma. (2,3) Because individuals with CPA more often have postoperative complications, such as prolonged air leak, empyema, and bleeding, mortality is higher in CPA than in SPA. (3,5,9,10) Because of the impaired immunity of patients undergoing chemotherapy, patients on corticosteroid therapy, diabetic patients, AIDS patients, and transplant recipients, as well as the high mortality associated with pulmonary mycoses, clinicians and surgeons should focus on the diagnosis and management of complications in pulmonary aspergilloma and in other pulmonary mycoses.…”
mentioning
confidence: 99%
“…Kronik malnutrisyon, kronik obstruktif akciğer hastalığı ve parankimal akciğer hastalığı da risk faktörlerindendir [2]. Tü-berküloz, sıkı plevral adhezyonlar ve hasta akciğer parankimi aspergillomada standart akciğer rezeksiyonu sonrası mortalite oranını arttıran faktörlerdir [6]. Postoperatif morbidite aşırı kanama, uzamış hava kaçağı, rezidüel plevral boşluk, bronkoplevral fistül ve ampiyemi içerir [6].…”
Section: Discussionunclassified
“…Tü-berküloz, sıkı plevral adhezyonlar ve hasta akciğer parankimi aspergillomada standart akciğer rezeksiyonu sonrası mortalite oranını arttıran faktörlerdir [6]. Postoperatif morbidite aşırı kanama, uzamış hava kaçağı, rezidüel plevral boşluk, bronkoplevral fistül ve ampiyemi içerir [6]. Ciddi plevral boşluk enfeksiyonunun tedavisinde ve bronkoplevral fistül tamiri için ekstratorasik kas flebi kullanılabilir [2].…”
Section: Discussionunclassified